Multivalued evolution equations with infinite delay in Fréchet spaces - Selma BAGHLI-BENDIMERAD; Mouffak Benchohra (Electronic Journal of Qualitative Theory of Differential Equations, 2008)
In this paper, sufficient conditions are given to investigate the existence of mild solutions on a semi-infinite interval for two classes of first order semilinear functional and neutral functional differential evolution inclusions with infinite delay using a recent nonlinear alternative for contractive multivalued maps in Fréchet spaces due to Frigon, combined with semigroup theory.